Connecting theory of plasmoid-modulated reconnection to observations of solar flares. (25th November 2022) - Camera, Stefano; Hillier, Andrew; Takasao, Shinsuke
Abstract: The short timescale of the solar flare reconnection process has long proved to be a puzzle. Recent studies suggest the importance of the formation of plasmoids in the reconnecting current sheet, with quantifying the aspect ratio of the width to length of the current sheet in terms of a negative power α of the Lundquist number, that is, S^-α , being key to understanding the onset of plasmoids formation. In this paper, we make the first application of theoretical scalings for this aspect ratio to observed flares to evaluate how plasmoid formation may connect with observations. For three different flares that show plasmoids we find a range of α values of α =0.26 to 0.31 . The values in this small range implies that plasmoids may be forming before the theoretically predicted critical aspect ratio ( α =1/3 ) has been reached, potentially presenting a challenge for the theoretical models.